Device-assisted enteroscopy: An update on techniques, clinical indications and safety. Issue 7 (July 2019) - Pennazio, Marco; Venezia, Ludovica; Cortegoso Valdivia, Pablo; Rondonotti, Emanuele
Abstract: After more than 15 years since its introduction into clinical practice, indications for device-assisted enteroscopy have greatly expanded. Alongside the consolidated indications such as the diagnosis and treatment of small bowel bleeding, Crohn's disease, hereditary polyposis, small-bowel tumors and complicated celiac disease, device-assisted enteroscopy is nowadays largely used to perform endoscopic retrograde cholangiopancreatography in patients with altered anatomy, stent placement, retrieval of foreign bodies, direct insertion of jejunal feeding tubes, and in selected cases of incomplete colonoscopy. This has been made possible by the technical improvements of the enteroscopes and accessories and by the widespread use of the method. Device-assisted enteroscopy endotherapy currently offers a safe and effective alternative to major surgery and often represents the preferred option for treatment of small-bowel pathology. Its safety profile is favourable even in the elderly patient, provided that it is performed in high-volume and experienced centers. The evolution of the enteroscopy technique is a challenge for the future and could be facilitated by the new enteroscopes models. These prototypes need a thorough clinical and safety assessment especially for the complex therapeutic procedures. Large prospective, multicenter studies should be performed to assess whether the use of device-assisted enteroscopy leads to improved patients' long-term outcomes.